2022
DOI: 10.3390/toxins14100714
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Enniatin A on Steroidogenesis and Proliferation of Bovine Granulosa Cells

Abstract: The emerging Fusarium mycotoxins enniatins (ENNs) have been the focus of new research because of their well-documented existence in various cereal and grain products. Research findings indicate that reproductive disorders may be caused by exposure to Fusarium mycotoxins, but little work has evaluated ENNs on reproductive function. Therefore, to determine the effects of ENNA on the proliferation and steroidogenesis of granulosa cells (GC), experiments were conducted using bovine GC cultures. In vitro, ENNA (1–5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Interestingly, in the same study, the level of transcribed genes also showed down-regulation of the HMGR , CYP11A , HSD3B2 , and CYP17A1 genes. In line with our results for cholesterol quantification, Chiminelli et al (2022) showed a sudden but non-dose-dependent reduction in the amount of progesterone or estradiol on the small follicle GC [ 53 ]. The study by Payne and Hales (2004) showed the link between the cholesterol pathway and steroid hormones [ 56 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, in the same study, the level of transcribed genes also showed down-regulation of the HMGR , CYP11A , HSD3B2 , and CYP17A1 genes. In line with our results for cholesterol quantification, Chiminelli et al (2022) showed a sudden but non-dose-dependent reduction in the amount of progesterone or estradiol on the small follicle GC [ 53 ]. The study by Payne and Hales (2004) showed the link between the cholesterol pathway and steroid hormones [ 56 ].…”
Section: Discussionsupporting
confidence: 91%
“…These down-regulated genes had an indirect effect on the steroid hormone biosynthesis pathway, impacting overall hormone production. Chiminelli et al (2022) studied the effect of ENN A on ovarian bovine cell function, and concluded that steroid production was inhibited [ 53 ]. Other studies on fumonisin 1 and BEA in bovine cells showed a decrease in the expression of CYP11A1 and CYP19A1 genes [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Star, Cyp11a1, Cyp17a1, and Cyp19a1 are key genes in E 2 and Pg synthesis, and Sf-1 stimulates the expression of almost all genes involved in cholesterol mobilization and steroid hormone biosynthesis [ 10 ]. Many studies have shown that the expression of hormone synthesis genes changes to different extents when steroid hormone levels change after exposure to chemicals in the body, so genes in the hormone synthesis pathway are often important targets for chemicals, which affects hormone synthesis [ 11 , 12 ]. During hormone synthesis disorder in ovarian GCs of F1 offspring exposed to Cd during pregnancy, the above hormone synthesis-related genes also showed different degrees of changes and were closely related to hormone phenotypic changes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, effects on cell viability and apoptosis induction were observed by the high permeation from blood to the brain across the blood-brain barrier [ 7 ]. Recent evidence suggests that Enniatin B (ENNB) can produce Reactive Oxygen Species (ROS) targeting the intestinal barrier [ 8 ], affecting the embryonic development in mice [ 9 ], and impairing the reproductive function of cattle in vitro [ 10 ]. An interactive effect of ENNB with DON has been observed in piglets, which in combination led to decreased weight gain and diversity of gut microbiome [ 11 ].…”
Section: Introductionmentioning
confidence: 99%